Some inverse problems for parabolic and elliptic differential-operator equations - Eydelman, S. D. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Necessary and sufficient conditions are established for the unique solvability of problems of determining an unknown right-hand side of a differential equation with an unbounded operator coefficient under an additional boundary condition.